Analisis Sistem Informasi Akuntansi Penerimaan atas Tagihan Pembayaran Member Parkir Secara Virtual Account - Nanik Nur Istiqomah; Rafika Ludmilla (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
This research aims to find out how the accounting information system for receipt of parking member payment bills using a virtual account which is carried out at PT Securindo Packtama Indonesia Area Rukan PIK is running well or not and what the internal controls are at the company. The research method used is the qualitative analysis method. The data collection techniques used in this research are observation, interviews and documentation. The results of this research are based on analysis of the accounting information system and internal control system, where the system used by the company is good because it has helped record receipts for parking member payment bills quite efficiently in terms of time, while the company's internal control system is also quite good, although still duplicate tasks were found in certain sections.